Seleksi Daya Hasil Empat Isolat G5 Jamur Merang (Volvariella volvaceae) Faperta Unsika di Kecamatan Majalaya Kabupaten Karawang - Rahmatolloh, Fajrin Rizky; Purnomo, Sulistyo Sidik; Lestari, Ani (JURNAL AGROPLASMA, 2024)
The success of merang mushroom cultivation is determined by the use of quality seeds. Mushroom farmers in Karawang Regency still have difficulty in getting superior seeds at a quality price. Efforts to overcome this are by procuring superior seeds for merang mushroom cultivators in Karawang Regency. The isolate of prospective seedlings G5 of Faperta Unsika merang mushroom is the result of a cross between white merang mushroom elders from Cilamaya Kulon and semi merang mushroom elders from Purwasari, each of which has advantages. The purpose of this study was to obtain the best G5 isolate of merang mushroom (Volvariella volvaceae) Faperta Unsika that can be used as a candidate for propagation seedlings. This research used a barn measuring 6 m x 4 m in Pasir Buah Hamlet, Pasir Mulya Village, Majalaya District, Karawang Regency which was carried out for 2 months from April 2024 to May 2024. The research method used was Single Factor Randomised Group Design (RAK) with 6 treatments namely A (G5 FP SEMI), B (G5 FP WHITE), C (G5 FP 005), D (G5 FP 003), E (G5 FP 021), F (G5 FP 034). All treatments were repeated 5 times. The results showed that there was no real effect of selection of four G5 isolates of merang mushroom FP Unsika.. Keywords : g5 faperta unsika isolate, straw mushroom, superior seeds